Improvement of sperm motility of Oncorhynchus mykiss and Salvelinus fontinalis by L-tryptophan. (4th May 2019) - Kocabaş, Mehmet; Kutluyer, Filiz; Ertekin, Özlem; Aksu, Önder; Başçınar, Nadir
ABSTRACT: Experiments were designed to test the influence of L-tryptophan supplementation of the extender on the sperm motility parameters and bacterial flora of brook trout ( Salvelinus fontinalis ) and rainbow trout ( Oncorhynchus mykiss ). The extender containing 0.3 M glucose in 10% Dimethyl sulfoxide (DMSO) was supplemented with 0, 0.5, 1, 2, and 4 mM L-tryptophan. Sperm samples stored for up to 12 days at 4°C for brook trout were motile while motility was not observed after six days of storage for rainbow trout. Diluted sperm samples were spread-plated onto Plate Count Agar (PCA) (Total Bacteria Count), Rose Bengal Agar (RBC) (Yeast-Mold Count), Violet Red Bile Dextrose (VRBD) ( Enterobacteriaceae count) and Mannitol Salt Agar (MSA) ( Micrococcus/Staphylococcus count) and counts were performed in duplicate and sampling occurred on day 0, 2, 4, 6, and 12 of cold storage. L-tryptophan supplementation of the extender yielded a positive effect, significantly prolonging sperm motility in S. fontinalis and O. mykiss compared to the control group ( p < 0.05). The ideal results were obtained above a concentration of 0.5 mM for both species. Total bacteria count in fresh sperm (undiluted samples) was not detectable and not detected in sperm samples treated with different L-tryptophan concentrations. Yeast-mold, Enterobacteriaceae and Micrococcus/Staphylococcus were not detected from fresh and treated sperm brook trout and rainbow trout. On the basis of the results, L-tryptophan-based extender is useful for maintaining sperm quality in short-term storage. L-tryptophan had a negative effect on the bacterial flora. The results of the current study encourages further studies related to long-term storage and reproduction management. Abbreviations: DMSO: dimethyl sulfoxide; PCA: plate count agar; RBC: rose Bengal agar; VRBD: violet red bile dextrose; MSA: mannitol salt agar; SCA: sperm class analyzer; CFU: colony-forming unit